Myths of the 130 Quarter - Kozma Kvartalov (Проект Байкал, 2016)
We continue to publish the myths of the 130 Quarter. They are told by an honored crooner, collector of the modern city folklore Kozma Kvartalov. Please do not treat his stories as historical accounts. They are more like fairy tales where the historical truth is interlaced with contemporary fiction. The occurrence of such myths evidences a vivid interest and development of the city. Or at least a city quarter.